Knowledge and utilization of Indian system of Medicine in the state of Assam - Yadav, Ram Janak; Yadav, Jeetendra; Siddique, Niyamat; Pandey, Arvind (Indian Journal of Community Health, 2015)
Background: As no study was available about the usage of Indian system of Medicine and homoeopathy in North eastern states accordingly Indian Council of Medical Research entrusted this study to this Institute. Aims & Objective: To know the knowledge, attitude and practices of Indian system of Medicine and homoeopathy in Assam state. Material & Methods: To achieve these objectives, Fifty villages were selected from each selected district for Assam states. Twenty households with at least one member ill during the last three months and availed medical care services for treatment have been selected from each village. About 3,000 households were covered to know their perception about the ISM&H. From these households in all, 4800 sick persons (who fell sick in last three months) and taken any treatment were interviewed. Results: More than three fourth of the household are being headed by male members. About 40 percent of households reported to have visited traditional healers at the time of their illness. Bone setting (37%), Dog bite (23%), Jaundice (20%), Measles (16%), Sciatica (9%) and Snake bite (5%). Jaundic, Sciatica, Measles and Migraine were the illnesses for which the patients also visited traditional healers. As a whole, ISM&H was preferred in Government setup by 65% in case of normal ailments but in case of serious ailments, assistance preferred for Government was about 25%. Allopathy system was more preferred in case of serious ailments as compared to Ayurveda in normal ailments which were about 45%.